2017
DOI: 10.3758/s13428-017-0963-x
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive reflection test is robust to multiple exposures

Abstract: The cognitive reflection test (CRT) is a widely used measure of the propensity to engage in analytic or deliberative reasoning in lieu of gut feelings or intuitions. CRT problems are unique because they reliably cue intuitive but incorrect responses and, therefore, appear simple among those who do poorly. By virtue of being composed of so-called Btrick problems^that, in theory, could be discovered as such, it is commonly held that the predictive validity of the CRT is undermined by prior experience with the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 33 publications
4
78
0
1
Order By: Relevance
“…First, even though our items have low initial familiarity, with the continuous use of the measure, familiarity will become an issue. Our research did not establish whether familiarity will be detrimental to the predictive validity of the Verbal CRT or whether it will only have a negligible effect on predictive validity as has been demonstrated recently with the Numerical CRT (Bialek & Pennycook, 2017;Meyer et al, 2018). Future research should address the issue of previous exposure and its effect on predictive validity.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…First, even though our items have low initial familiarity, with the continuous use of the measure, familiarity will become an issue. Our research did not establish whether familiarity will be detrimental to the predictive validity of the Verbal CRT or whether it will only have a negligible effect on predictive validity as has been demonstrated recently with the Numerical CRT (Bialek & Pennycook, 2017;Meyer et al, 2018). Future research should address the issue of previous exposure and its effect on predictive validity.…”
Section: Discussionmentioning
confidence: 47%
“…Second, an increasing proportion of participants are already familiar with the CRTin terms of prior exposure as well as in terms of knowledge of the items. Self-reported prior exposure substantially increased the average performance in the test (e.g., Bialek & Pennycook, 2017;Haigh, 2016;Stieger & Reips, 2016). However, recent studies have reported that self-reported prior exposure did not diminish the predictive validity of the test (Bialek & Pennycook, 2017) and found no evidence that the actual prior exposure (not self-reported) increased the performance (Meyer, Zhou, & Frederick, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One limitation is that research pools may be polluted due to overexposure to the CRT items (Haigh, 2016). However, recent studies (i.e., Bialek & Pennycook, 2017) found that exposure does not negatively affect results. Further, we used a seven-item measure to address this issue as Haigh (2016) suggested.…”
Section: Limitationsmentioning
confidence: 99%
“…The CRT is widely used because it was uniquely designed to measure the intuitive thinking processes linked to cognitive biases (Frederick, 2005) and has been shown to predict variance beyond general mental ability (g) in decision-making outcomes (Toplak, West, & Stanovich, 2014). In addition, as concern over the influence of cognitive bias on decision making is growing (e.g., Comaford, 2016;National Research Council, 2015), the CRT has received increased attention as a meaningful predictor of susceptibility to cognitive heuristics in both the scientific community (e.g., Bialek & Pennycook, 2017) and the general public (e.g., Cowen, March 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We also added the 7-item expanded version of the Cognitive Reflection Test (CRT; Toplak, West, & Stanovich, 2014) in Study 2 to examine if individual differences in cognitive capability could be related to percentile miscalibration. We chose the CRT because it has shown to be significantly associated with numeracy (Bialek & Pennycook, 2018;Liberali, Reyna, Furlan, Stein, & Pardo, 2012) and metacognitive monitoring (Mata, Ferreira, & Sherman, 2013;Pennycook, Ross, Koehler, & Fugelsang, 2017). Performance on the CRT can also be used as a metric of general mental ability (Blacksmith, Yang, Behrend, & Ruark, 2019), as well as a marker of people's willingness to think analytically and use their cognitive resources (Frederick, 2005;Šrol, 2018).…”
Section: Studymentioning
confidence: 99%